Primary Cutaneous Adenoid Cystic Carcinoma - KESKİN ÖZTÜRK, BEYZA; KAYA, CANER; DURMUŞ KOCAASLAN, FATMA NİHAL; ÇELEBİLER, ÖZHAN BEKİR; CİNEL, ZELİHA LEYLA (My University, 2020)
Adenoid cystic carcinoma is a malignant tumor usually localized in the salivary glands. It can also develop in serous glands such as the breast, main bronchi, uterine cervix, Bartholin's gland of the vulva, prostate gland, and external auditory canal. It is more common in the white race. Most of the primary cutaneous adenoid cystic carcinoma cases occur on the scalp. Despite the high rate of metastasis, long-term survival can be observed because the progression of the disease is slow. Distant organ metastases such as lungs, bone, liver and brain have also been reported in the literature at 40%. Its treatment is wide excision of the lesion and demonstration of tumor negative margin in pathological sampling. In this case report, we wanted to present surgical and oncological treatment to a 65-year-old female patient with lung metastasis diagnosed with adenoid cystic carcinoma on the scalp.